PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI STRES KERJA KERJA SEBAGAI VARIABEL INTERVENING PADA PT. ENERGI ENTELEMI INDONESIA - Asri Ayu Adisti; Ni Nyoman Sawitri, Dovina Navanti, Hapzi Ali, Muhammad Asif Khan (ADISAM PUBLISHER, 2024)
This research aims to determine the effect of workload and compensation on employee performance through work stress at PT. Indonesian Entelemic Energy. The research method used is quantitative research. The population in this study was 50 respondents in accordance with the total number of employees. The sample in this research is a saturated sample in which the entire population was surveyed. The data collection procedure in this research was to use a questionnaire using a Likert scale and Smart PLS 4.1 software programming. The data analysis techniques used are outer model analysis, inner model analysis and hypothesis testing. The research results show that: (1) workload has a significant effect on work stress in the company PT. Energi Entelemi Indonesia, (2) compensation has a significant effect on work stress at the company PT. Energi Entelemi Indonesia, (3) workload has no effect on employee performance at the company PT. Energi Entelemi Indonesia, (4) compensation has a significant effect on employee performance at the company PT. Energi Entelemi Indonesia, (5) work stress has no significant effect on employee performance at PT. Indonesian Entelemic Energy.